CYTOPLASMIC AND PLASMA-MEMBRANE ULTRASTRUCTURE OF PARACOCCIDIOIDES-BRASILIENSIS YEAST-PHASE CELLS AS REVEALED BY FREEZE-ETCHING - Takeo, K.; Sano, A.; Nishimura, K.; Miyaji, M.; Franco, M.; Kanetsuna, F. (Cambridge University Press, 1990)
Using a freeze-etch technique the cytoplasmic and plasma membrane ultrastructure of Paracoccidiodies brasiliensis yeast-phase cells was studied. The multinucleate yeast-phase cells which grow by simultaneous multiple budding, like those of Mucor sp. contain several nuclei, mitochondria, well-developed ER, small vacuoles and lipid droplets. Complex structures with no apparent connexion to the plasma membrane of P. brasiliensis usually lack inveginations, but invaginations which do occur are always rod-shaped which indicates P. brasiliensis to be of either ascomycetous or basidiomycetous origin.
Keywords: PARACOCCIDIOIDES-BRASILIENSIS; ULTRASTRUCTURE; PLASMA MEMBRANE; FREEZE-ETCHING